Checkerboard Target Measurement in Unordered Point Clouds with Coloured ICP - J. M. Goo; J. Li; D. Wicaksono; J. Boehm (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
In this work we investigate the problem of measuring a checkerboard target’s centre in an 3D point cloud. This is an important problem which has applications in registration, long term monitoring and linking to other sensor systems. We use a 3D template matching approach based on the coloured ICP algorithm to solve the problem. We tackle the problem under the additional constraints that we assume no structure in the 3D data in order to be able to handle unordered point clouds. This gives us the capability to process data from the new generation of low-cost LIDAR sensors. This category of sensors also suffers from increased noise in range and reflectivity measurement. We provide extensive simulation results using synthetic data to capture the potential of the approach. We then give the detailed steps for handling real sensor data.